Do Private Firms Outperform SOE Firms after Going Public in China Given their Different Governance Characteristics? - Shenghui Tong; Eddy Junarsin (Gadjah Mada International Journal of Business, 2013)
This study examines the characteristics of board structure that affect Chinese public firm’s financial performance. Using a sample of 871 firms with 699 observations of previously private firms and 1,914 observations of previously state-owned enterprise (SOE) firms, we investigate the differences in corporate governance between publicly listed firms that used to be pure private firms before going public and listed firms that used to be SOEs before their initial public offerings (IPOs). Our main finding is that previously private firms outperform previously SOE firms in China after IPOs. In the wake of becoming listed firms, previously SOE firms might be faced with difficulties adjusting to professional business practices to build and extend competitive advantages. In addition, favorable policies and assistance from the government to the SOE firms might have triggered complacency, especially in early years after getting listed. On the other hand, professional savvy and acumen, combined with efficiency and favorable business climate created by the government have probably led the previously private firms to improve their values stronger and faster.